Effect of Adrenocorticotropic Hormone Stimulation During Simultaneous Bilateral Adrenal Vein Sampling in Primary Aldosteronism - Liu, Wei; Zhang, Jingjing; Yang, Yaling; Jin, Yinxin; Li, Zaizhao; You, Liting; Luo, Jianguang; Su, Xin (Hormone and Metabolic Research, 2021)
The aim of the study was to investigate the significance and influence of adrenocorticotropic hormone (ACTH) stimulation in primary aldosteronism (PA) patients with simultaneous bilateral adrenal vein sampling (AVS). All patients diagnosed with PA underwent simultaneous bilateral AVS with ACTH. In 95 patients, the post-ACTH SI significantly increased (p<0.001), and it gradually decreased from t10–t30 after ACTH stimulation (p<0.001). The unsuccessful catheterization decreased after ACTH stimulation. Time points within 20 min after ACTH stimulation were better for sampling, and the selectivity did not increase over longer periods. According to lateralization before and after ACTH stimulation, the patients could be divided into 3 groups (U, unilateral; B, bilateral): U/U , U/B or B/U, and B/B. Compared with the U/U group, in the U/B or B/U and B/B groups, the lateralization index (LI) was lower both at baseline and after ACTH stimulation (p<0.0001), the contralateral index (CLI) was higher after ACTH stimulation (p<0.003), the serum potassium level was higher (p<0.001), and the carbon dioxide combining power (CO2CP) and base excess (BE) levels were lower. In conclusion, in simultaneous bilateral AVS, ACTH stimulation had significant effects on increasing the catheterization selectivity. Lateralization change was observed after stimulation. After ACTH stimulation, fewer patients could be diagnosed with lateralized PA. Patients with consistent lateralized PA showed a more serious phenotype.
Keywords: primary aldosteronism; adrenal vein sampling; ACTH stimulation; selectivity index; lateralization index